A review on quality from the perspective of industrial product design assessment - Craciun, Alexandra Elena (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
The design assessment of an industrial product implies the objective approach of the product from both technical and aesthetic perspective, considering the market segment and its relation to the product through ergonomic and also signification associations, all of this taking into account functionality and the perceived quality of a product. The presented paper represents a review on quality in its relation to product design by analysing in turn the relations between quality, product, design and user and establishing the common concepts associated to quality related to each design dimension. The research contributes to the understanding of quality when is addressed from the point of view of industrial design assessment.